A Seismic Data Processing System based on Fast Distributed File System (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Big data has attracted an increasingly number of attentions with the advent of the cloud era, and in the field of seismic exploration, the amount of data created by seismic exploration has also experienced an incredible growth in order to satisfy the social needs. In this case, it is necessary to build a highly-effective system of data storage and process. In our paper, we aim at the properties of the seismic data and the requirement to the performance of IO, and establish a distributed file system with the goal of processing seismic data based on the Fast Distributed File System (Fast DFS), then test our system through a series of operations such as file write and read, and the results show that our file system is very proper and effective when processing seismic data.